Free From What - Papanikolaou, Maria (My University, 2023)
The exhibition – Maria Papanikolaou’s first solo show in Greece – includes new works especially for the industrial space of the Service Yard. Minimalist in situ interventions, sculptural installations and video installations will be presented in an imperceptibly dialogical relationship with each other, creating a low-voiced poetic universe. The ambiguous title phrase [free/of what], suspended between question and statement, sets the tone for the internal, deeply reflective nature of the exhibition. The artist herself says of her works: “I make models and sculptures that depict spaces of potential escape, but also resilient tools that bear witness to imaginative ways of disentanglement and escape. Throughout human history, thousands of people have tried to escape from slavery, war, poverty, authoritarian regimes, concentration camps and prisons of all kinds. Combining data with imagination, my work traces through a variety of forms whether the stories of these people can be turned into a kind of textbook for the recovery of human freedom. In Art History we often see the incarcerated person presented as a passive victim who evokes our pity and sympathy. My artistic production is instead based on a series of experiments aimed at presenting man as that creative subject who invents ways of escape, satisfying his basic instinct for life and freedom. The works I am exhibiting are therefore proposals to break the bonds that may pin each or every one of us down in different states of unfreedom.”